SISTEM MEMPERTAHANKAN IDEOLOGI BANGSA INDONESIA DI ERA PERUBAHAN MASYARAKAT (Studi Desa Baru Kecamatann Pancur Baru, Kabupaten Deliserdang) - Masrul; Andini; Ana; Diva; Fatila; Fitri; Ikrima; Lilya; Marwah; Senja; Wafid (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
The Pancasila ideology has five sasa, or grounds, and is the fundamental philosophy of the Indonesian state. Pancasila is an umbrella term encompassing the following concepts: social justice for all Indonesians, democracy guided by wisdom in debate and representation, fair and civilized humanity, and almighty deity. The goal of pancasila philosophy is for Indonesia to grow and become a just, wealthy, and civilized country. The community, including common people, village leaders, and youths, does sense changes, according to the research results, but these changes still include national unity and unity since the community still strongly agrees with Pancasila.